EXPLORING AND EXPLAINING THE ECONOMIC POLITICAL RELATIONS BETWEEN IRAN AND THE SOVIET UNION IN THE SECOND PAHLAVI ERA EMPHASIZING THE SYSTEM THEORY - Zare, Kimia; Saeeidinia, Habibollah (Gênero & Direito, 2020)
Iran and Russia have common interests, especially in political terms, because of the common borders and territorial neighborhood. This has led to a specific sensitivity to how the two countries are approaching each other. Despite the importance of the two countries’ relations, it is observed that in the history of the relations between Iran and Russia, various issues and issues have always been hindered by the close relations between the two countries. The beginning of Iran-Soviet relations during the Second Pahlavi era was accompanied by issues such as World War II and subsequent events. The relations between the two countries were influenced by the factors and system variables of the international system, such as the Cold War, the US-Soviet rivalry, the Second World War and the entry of the Allies into Iran, the deconstruction of the relations between the two post-Cold War superpowers, and so on.The main question of the current research is that the political relations between Iran and Russia influenced by the second Pahlavi period?To answer this question, the hypothesis was that Iran’s political economic relations were fluctuating in the second Pahlavi era and influenced by the changing system theory of the international system with the Soviet Union. The findings suggest that various variables such as the structure of the international system and international events, including World War II, the arrival of controversial forces in Iran, the Cold War, the post-Cold War, the US and Soviet policies, and the variables such as the issue of oil Azerbaijan’s autonomy, Tudeh’s actions in Iran, the issue of fisheries and borders. Also, the policies adopted by Iranian politicians, including negative balance policy, positive nationalism and independent national policy, have affected Iran-Soviet relations. In a general conclusion, from 1320 (1942) to 1357 (1979), the relationship between Iran and Russia has been an upward trend towards peaceful coexistence. But expansion of further relations in the economic, technical and cultural fields has been political rather than political.